Collective action: Issues and challenges - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Groups are of fundamental importance to economic, social, and political outcomes. Group formation among the poor may affect poverty directly, via improved income generation, or indirectly via empowerment and political action. Groups can be important vehicles for representing and promoting the interests of their members. In a number of significant ways, however, the chronically poor are disadvantaged in group formation, and this may form a significant part of the vicious circle and dynamics of chronic poverty.